Corneal defects: do they matter?. (24th May 2012) - McCall, K; Mohamed, H; Ellis, D; Gregory, M; Dutton, G; Richardson, J
Abstract : Introduction: Ocular defence mechanisms are challenged in the intensive care environment secondary to sedation, paralysis and mechanical ventilation. Defects may develop in the exposed cornea. These are painful, may cause agitation and can lead to bacterial keratitis, with potentially devastating effects on vision. Protective treatments are available but there are no universal guidelines for eye care. Literature review revealed a paucity of knowledge within the paediatric population. Aims: Establish incidence and risk factors for development of corneal defects within a paediatric intensive care (PICU) population. Directly assess the effect of the introduction of an eye care guideline. Methods: A prospective audit was undertaken. Weekly eye examinations of all mechanically ventilated children were performed by an ophthalmology SpR and intensive care fellow. Current eye care, eyelid position and presence of any corneal abnormalities were assessed. New eye care guidelines were developed and introduced by means of tutorials, bedside demonstrations and posters. Repeat audit assessed improvements in eye care. Results: 45 children were examined prior to implementation of the new guidelines. 33.3% had defects in at least one eye. 20% had bilateral defects. Incomplete eye closure and longer stay increased the risk of defect development. 80% were receiving no formal eye care, and when used treatment choices were inconsistent. 37 children were examined following introduction of the new guidelines. 35 (94%) received formal eye care according to the protocol. There was a significant reduction in the incidence of corneal defects (p=0.019), 10.8% having a defect in at least one eye and 5.4% bilateral defects. Although rates of incomplete eye closure were not reduced, there was a significant reduction in the incidence of defects within incompletely closed eyes (86.7% vs 19.9%). All patients with defects commenced regular simple eye ointment and had complete resolution at follow-up. Implications: Corneal defects are a source of unrecognised morbidity within PICU. Simple preventive measures are available. Use of eye care guidelines reduces the incidence of corneal defects. Vigilant eye care is essential for all intensive care patients.